“Análisis comparativo del tratamiento de contenidos informativos de las ediciones impresas y digitales de diario regional los Andes, período enero - junio 2019” - Erika Gabriela, Cajo Pillajo (2020)
The development of this research titled "A COMPARATIVE ANALYSIS OF THE PROCESSING OF INFORMATIVE CONTENTS OF THE PRINTED AND DIGITAL EDITIONS OF THE REGIONAL NEWSPAPER "LOS ANDES", PERIOD JANUARY - JUNE 2019" was carried out with the aim of understanding the logic of production and distribution of informative content that the newspaper had for the printed medium and the digital platform. For this research we worked with analytical, field, scientific, descriptive and bibliographic documentary methods, it is qualitative, it was not required the application of the population and sample, we analyzed each of the notes, comparing the journalistic genre, location, graphical support elements among other components. The techniques used were documentary review, content analysis, observation and interviews, each with its own tools. 1330 notes were analyzed, concluding that the contents published in the printed medium and on the digital platform are the same in form and in message, this situation does not work from the point of view of the interviewees because they do not have a message prepared according to the medium in which it is published. Newspaper executives recognize the error and mention that the processing and distribution of content will be improved to meet the audience’s requirements. For this reason, we propose a Manual for the distribution of content through the Web with the aim of improving the logic of distribution of informative content, taking advantage of all the tools offered by the Web and thus satisfying the needs of the people.